The pleasure of the voice (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
The text develops a reflection within the scope of the relations between voice and experience, discussing the pleasure of the voice, in confrontation with fear and voice work. Along the way, in which the pleasure of the voice leads to pleasure in the theater, the author essays dialogues with the writer Roland Barthes (The pleasure of the text) and theatrical artists, such as Cicely Berry (Voice and the Actor), Isabel Setti (The body of the word it is not fixed, it lets itself be touched by time and its spaces) and Bertolt Brecht (Small Organon for the Theatre). It is an itinerary to meet the pleasure of the voice that vibrates, cuts, historicizes and astonishes.
Keywords: voice; pleasure; work; astonishment; contemporary vocality